Epidemics in the holy quran a study of causes and treatments - Chasib ghazi rashak ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Noble Qur’an is the approach of the Creator and the eternal miracle of the Messenger by which the righteousness of humanity lies in the society in every time and place. Whoever follows it has achieved the goal and happiness. It is the constitution and method of Islamic Sharia, which has set for humanity a scientific and educational approach to educating, educating and purifying man to reach his spiritual and physical perfection. Mental and physical health and the causes of chronic diseases and epidemics, developing solutions and preventing them through an integrated system through the Qur’anic cultural guidelines and awareness that set the boundaries and barriers between man and his behavior to prevent the damages that occur and are expected throughout history In this study, the research deals with epidemics in the Qur’an, studying the causes of human behavior and not taking care of purities and impurities and other abominations that cause diseases and how to prevent and treat them through the Qur’anic approach and Islamic law